Cross training: indices of training stress and performance - Flynn, M. G.; Carroll, K. K.; Hall, H. L.; Bushman, B. A.; Brolins, P. G.; Weideman, A. (Medicine & Science in Sports & Exercise, 1998)
Twenty well-trained runners (VO2max 4.6 ± 0.5 L·min-1) were age and ability matched and assigned to either a cross training (CT) or run only group (RT). RT and CT responded similarly to 6 wk of increased training, and both groups improved 5-km performance to a similar extent. (see also http://www-rohan.sdsu.edu/dept/coachsci/vol12/flynn.htm)